A educação continuada do catalogador: o caso da Universidade do Estado de Santa Catarina Cataloguer´s continued education: the case of the Santa Catarina State University p. 219-239 - Pereira, Ana Maria; Rodrigues, Renata (Revista ACB, 2005)
Apresenta os resultados da pesquisa feita para verificar as formas usadas pelos catalogadores das bibliotecas universitárias da Universidade do Estado de Santa Catarina, Brasil, para continuar sua educação profissional, comparando sua práticas com aquelas relatadas na literatura da área. Abstract: This paper presents the results of the research made inorder to verify the ways used by the catalogers of the University of libraries of the University of the State of Santa Catarina, Brazil, to continue their professional education comparing their practices with those related in the literature of the area. Keywords: Cataloging; Professional continuede education; Cataloging – University of the State of Santa Catarina (Brazil) net; Computer library cataloging – University oh the State of Santa Catarina, Brazil.